Answer:
x= ![-2 \pm \sqrt{13}](https://tex.z-dn.net/?f=-2%20%5Cpm%20%5Csqrt%7B13%7D)
Step-by-step explanation:
Given: ![3x^{2} -12x+27= 0](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20-12x%2B27%3D%200)
This is a quadratic equation.
![3x^{2} -12x+27= 0](https://tex.z-dn.net/?f=3x%5E%7B2%7D%20-12x%2B27%3D%200)
Taking common 3 from the equation given
⇒ ![3(x^{2} -4x+9)=0](https://tex.z-dn.net/?f=3%28x%5E%7B2%7D%20-4x%2B9%29%3D0)
dividing both side by 3
⇒
By using different factor, we can observe this trinomial can not be factored.
∴ solving it by completing the square.
⇒ ![x^{2} -4x+9=0](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-4x%2B9%3D0)
adding 9 on both side
⇒ ![x^{2} -4x= 9](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-4x%3D%209)
To get a perfect square number as coeffecient of x is 4, lets add both side by 4.
⇒![x^{2} -4x+4= 13](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-4x%2B4%3D%2013)
we know, ![(x+2)^{2} = x^{2} +2\times x\times 2+2^{2}](https://tex.z-dn.net/?f=%28x%2B2%29%5E%7B2%7D%20%3D%20x%5E%7B2%7D%20%2B2%5Ctimes%20x%5Ctimes%202%2B2%5E%7B2%7D)
∴ ![(x+2)^{2} =13](https://tex.z-dn.net/?f=%28x%2B2%29%5E%7B2%7D%20%3D13)
Taking Square root on both side, remember; √a²= a
⇒ ![(x+2)= \sqrt{13}](https://tex.z-dn.net/?f=%28x%2B2%29%3D%20%5Csqrt%7B13%7D)
opening parenthesis
⇒ ![x+2= \sqrt{13}](https://tex.z-dn.net/?f=x%2B2%3D%20%5Csqrt%7B13%7D)
subtracting both side by 2
∴ x= ![-2 \pm \sqrt{13}](https://tex.z-dn.net/?f=-2%20%5Cpm%20%5Csqrt%7B13%7D)